Dual Task Performance in Parkinson’s Disease - Jennifer A. Foley; Reiner Kaschel; Sergio Della Sala (Behavioural Neurology)
Several studies have found dual tasking to be impaired in Alzheimer's disease (AD), but unaffected by healthy ageing. It is not known if this deficit is specific to AD, or also present in other neurodegenerative disorders that can occur in later life, such as Parkinson's disease (PD). Therefore, this study investigated dual tasking in 13 people with PD, 26 AD and 42 healthy age-matched controls. The people with AD demonstrated a specific impairment in dual tasking, which worsened with increasing disease severity. The people with PD did not demonstrate any deficits in dual tasking ability, when compared to healthy controls, suggesting that the dual task impairment is specific to AD.